Mammalian Retromer Is an Adaptable Scaffold for Cargo Sorting from Endosomes - Kendall, Amy K.; Xie, Boyang; Xu, Peng; Wang, Jue; Burcham, Rodger; Frazier, Meredith N.; Binshtein, Elad; Wei, Hui; Graham, Todd R.; Nakagawa, Terunaga; Jackson, Lauren P. (Structure (London), 2020)
Metazoan retromer (VPS26/VPS35/VPS29) associates with sorting nexins on endosomal tubules to sort proteins to the trans-Golgi network or plasma membrane. Mechanisms of metazoan retromer assembly remain undefined. We combine single-particle cryoelectron microscopy with biophysical methods to uncover multiple oligomer structures. 2D class averages reveal mammalian heterotrimers; dimers of trimers; tetramers of trimers; and flat chains. These species are further supported by biophysical solution studies. We provide reconstructions of all species, including key sub-structures (∼5 Å resolution). Local resolution variation suggests that heterotrimers and dimers adopt multiple conformations. Our structures identify a flexible, highly conserved electrostatic dimeric interface formed by VPS35 subunits. We generate structure-based mutants to disrupt this interface in vitro. Equivalent mutations in yeast demonstrate a mild cargo-sorting defect. Our data suggest the metazoan retromer is an adaptable and plastic scaffold that accommodates interactions with different sorting nexins to sort multiple cargoes from endosomes their final destinations. [Display omitted] •The metazoan retromer heterotrimer forms dimers, tetramers, and chains•Cryo-EM and biophysical studies reveal an electrostatic VPS35 dimer interface•Targeted structure-based point mutations disrupt the VPS35 interface in vitro•Structural data suggest that retromer is an adaptable scaffold Retromer is an important trafficking complex linked to human brain disease, but structures and mechanisms of metazoan retromer assembly remain elusive. Kendall et al. combine single-particle cryo-EM with biophysical studies to demonstrate that retromer forms multiple flexible oligomers. Mutagenesis confirms a key electrostatic dimer interface mediated by VPS35 subunits.